Ambang Batas Erosi Pada Suatu Daerah Aliran Sungai (Studi Kasus di DAS Tulis, Banjarnegara, Jawa Tengah) - Beny Harjadi; Inkorena G. S. Sukartono; Etty Hesthiati (Universitas Lambung Mangkurat, 2020)
Watersheds (DAS), which are river basins flowing in one outlet and limited by hills and mountains, often occur in land degradation or erosion. Erosion that occurs is said to be safe if it does not exceed the tolerable erosion or erosion tolerance limits or often called T-values. With regard to problems on sloping land in a watershed, the purpose of this study is to calculate the value of T-values or erosion tolerance limits. Calculation of T-values using the Hammer method (1981), namely by observing the factors of soil depth and effective depth of roots, and resources life of 300 or 400 years. T-value results are classified into 4 classes, namely (tons/ha/year) : (1) very low (<5), (2) low (5-25), (3) high (25-50), and (4) very high (> 50). The research location in the Tulis watershed is 12,750 ha in DTW (Reservoir Catchment Area) Mrica Banjarnegara. From the calculation of the T-value obtained results: very low 0.03% (3.8 ha), low 2.46% (313.7 ha), high 49.31% (6,287 ha), and very high 48.2% (6,145.5 ha).